The dynamic mechanical interactions associated with polyurethane baton rounds. - Stewart Peter Atkin (2002)
This thesis examines the important materials issues related to the design, improvement and biomedical assessment of baton rounds. In particular, it focusses on the time-dependent mechanical interactions between polyurethane and bone. The project initially deals with the mechanical behaviour of the polyurethane elastomers used for baton rounds. Using a variety of mechanical and environmental exposure tests, a better understanding is gained of the mechanical properties required for consistent performance. In particular, the importance of rebound resilience is identified when relating quasi-static quality control tests to impact behaviour. The thesis then concentrates on the dynamic mechanical properties of bone, with particular consideration to the measurement of shear modulus, which has been identified as a key parameter for modelling of baton round impacts. A combination of re-analysis of previously reported data and torsional testing of bovine scapulae samples has yielded a good understanding of the shear behaviour of bone and the effect of test rate. In addition, various synthetic bone materials have been characterised, in an attempt to design a bone simulant material that could be used for impact trials. This work has established the basis for a successful simulant based on fibre composites and polyurethane foam. The final section of the thesis comprises a brief examination of various options to design energy attenuating baton round systems that will further reduce the potential for head injury.